Two new species and a new record of stygobitic freshwater snails (Gastropoda, Cochliopidae) from Candela, Coahuila, northern Mexico - Czaja, Alexander; Becerra-López, Jorge Luis; Cordero-Torres, Diana Gabriela; Estrada-Rodríguez, José Luis; Cardoza-Martínez, Gabriel Fernando; Alonzo-Rojo, Fernando; Ávila-Rodríguez, Verónica (Zootaxa, 2024)
We describe two new species and a new record of stygobitic gastropods from small groundwater-fed springs in Candela, Coahuila, northern Mexico. Phreatomascogos garciasaucedoi n. sp. is described based on shell morphology and is the second species of this formerly monotypic genus. According to the current classification, we have transferred this genus to Cochliopidea. Phreatodrobia candelensis n. sp. is described, and represents the first record of the genus in Mexico extending its known range more than one hundred kilometers to the south. Also found with the new stygosnails was Coahuilix hubbsi Taylor, 1966, which was previously known only as an endemic species from the neighboring Cuatro Ciénegas valley. The reported new subterranean snails are restricted in their distributions to two small water sources only a few meters long which flow directly into a touristic zone with swimming pools and other recreation areas. Using NatureServe Ranking, both new species were assigned as critically imperiled. The very limited distribution and negative anthropogenic impacts within the sites should draw special conservation attention for the reported stygobionts.